Analysis of Bull Sperm DNA Abnormalities Due to Cadmium Accumulation - Fuad Fitriawan (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2017)
Sperm abnormalities can occur by various causes. Abnormality of sperm is usually characterized by abnormal sperm motility and viability. This was caused by the inability of mitochondria on ATP-ase in producing ATP and ecto-enzyme Cik role in keeping the movement so that movement of sperm motility declines. Research that leads to total abnormal sperm DNA analysis is still rare. The purpose of this research was to get the results of the molecular characteristic picture of the overall characteristics of DNA loci that have abnormalities in bull sperm and get a picture of differences in overall DNA loci of abnormal and normal sperm. This research was conducted in October-December 2016. With the results of Group I consists of D, E with a percent similarity of 92.308%, group II consists of C and Group I with a percentage similarity of 50.125%, group II consists of A and B with a percent similarity of 100%, group II and group III with a percentage similarity of 0%. Based on the above data it can be concluded that the treatment A and B is not suspected to cause DNA damage compared to treatment C, D and E.